Nation-Building and Identity in Europe - Tzanelli, R. author. aut Link
XIV, 238 p.
Keywords: This book offers a provocative theorization of nationhood, focusing on the key role played by dialogic relations of hegemony, resistance and reciprocity in the birth of the modern European nation. The relationship between Greece and Britain at the end of the nineteenth century uncovers the linguistic construction of nationalism.